PREDIKSI EROSI DAERAH ALIRAN SUNGAI POBOYA - Leonidas Paarrang; Uswah Hasanah; Anthon Monde (Universitas Tadulako, 2016)
Land rehabilitation in Poboya Watershed should be done on the actual land erosion value in other to avoid intensive land degradation. This research has been conducted to determine and map erosion hazard level. The erosion hazard level was determinate by using USLE (Universal Soil Lost Equation) formula. The result of experiment showed that the low erosion hazard level in study area 371,2 Ha (5,5%), medium 3.483,4 ha (51,9%), high 11,8 ha (0,2%), and very high 2.848,8 ha (42,4%). In general, land with erosion hazard level of very high is located in middle watershed. The high value of erosion in Poboya Watershed area mainly due to the land cover factor and topography. Tolerable erosion in Poboya watershed 371,1 ha (5,51%) and intolerable 6.344 ha (94,4%). Land area Poboya Watershed 6.715,06 ha and total erosion 2.643.587,48 ton.yr-1 while tolerable erosion 73.259,97 ton.yr-1.